Exploring the Role of Financial Literacy as a Catalyst for Circular Economy Adoption in Rural MSMEs in Indonesia and ASEAN - Muhammad Ibnu Salam; Najmudin Najmudin (Faculty of Economics and Business, Jenderal Soedirman University, 2026)
This study aims to explore financial literacy as a key catalyst for accelerating the adoption of the circular economy among Micro, Small, and Medium Enterprises (MSMEs) in rural areas of Indonesia and ASEAN countries. Employing a descriptive qualitative approach through a literature review, the research specifically identifies the relationship between the financial literacy levels of MSME owners and their readiness to implement circular economy innovations. Key aspects discussed include financial management understanding, capacity to access alternative funding sources, and challenges in integrating sustainability principles into everyday business practices. The literature review indicates that low financial literacy significantly hinders rural MSMEs' green investment decisions, while enhancing financial literacy is shown to strengthen MSMEs' capacity to effectively and sustainably adopt circular economy practices. The study underscores the importance of financial education strategies and community-based support programs as strategic initiatives that should be reinforced by government policies and multisectoral collaboration to ensure sustainable rural economic development in Indonesia and the ASEAN region.